The Difference of Anxiety Level and Family Support Between Congenital and Non Congenital People with Physical Disabilities in BBRSBD Prof. Dr. Soeharso, Surakarta - Desvian Adi Nugraha; Makmuroch .; Endang Sahir (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Anxiety arises due to various factors, like a state of physical disabilities. Family support is very important to eliminate those anxiety. This study aimed to know the difference of anxiety level and family support between congenital and non congenital people with physical disabilities in BBRSBD Prof. Dr. Soeharso, Surakarta.Method: This study is an observational analytic with cross-sectional study design. The study was held in BBRSBD Prof. Dr. Soeharso, Surakarta. The samples are 60 people consist of 30 congenital and 30 non congenital disabilities. The independent variable is congenital and non congenital disabilities. The dependent variables are the level of anxiety and family support. Samples were measured about their L - MMPI, TMAS and family support score. The results were tested by t test.Results: Statistical analysis for the study of t test in TMAS score has p value = 0.984 (> 0.05 ) so there is no difference of TMAS score significantly between congenital and non congenital disablility groups.While p value of family support is 0.115 (> 0.05), so there is no significant differences of family support between congenital and non congenital disablility groups.Conclusion:There is no difference of anxiety level and family support significantly between congenital and non congenital people with physical disabilities in BBRSBD Prof. Dr. Soeharso, SurakartaKeywords: Disability, anxiety, family support